(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The subject of the privacy of heritage took on great importance in the artistic levels of fashion designs because of its socially familiar knowledge formulations and its close connection to its structural and formal references, which made merging with the era a creative and innovative way commensurate with the continuous artistic changes and its intellectual and formal value to preserve the heritage identity and revive it through concepts and relationships Intertwined and consistent with contemporary thought in fashion design. Thus, a problem was identified through the following question: "What are the mechanisms of intellectual and applied integration between the privacy of heritage and contemporary trends in fashion design?" As for the importance of research, traditional fashion has artistic formations that stem from the breadth of material thought, cognitive awareness, and aesthetic formulas of privacy. Within a contemporary creative vision that can be used to revive the heritage and achieve communication and permanence on which the design formation of Arab fashion was based.The aims of the research: Knowing the concept of integration in design and revealing the specificity of heritage and the mechanisms of integration with contemporary design trends of Iraqi-Arab fashion.The limits of the research: the topic of merging in the design of Arab women’s fashion - Iraqi, Arab - with a specific heritage and its relationship to the concepts of contemporary trends in the light of the changing levels of intellectual and applied formal technology, within the time period 2017_2020.The research adopted the descriptive-analytical approach, and the research community included women’s fashion designs that carry the concepts of heritage specificity and the concept of intellectual and formal integration by adopting applied technical capabilities for contemporary materials and technologies. 22) an example. The research reached the most important conclusions, as follows:1. Contemporary trends in the design of traditional women’s fashion are considered a revitalizing process, which makes them appropriate to the developments of the times and in response to the requirements and needs of society, which confirms the existence of a common language in the design of traditional fashion, intellectually and practically.2. The integration between the creative intellectual awareness and the technical development and its performance capabilities was characterized by the design of the contemporary heritage dress, coinciding with the variables of culture and society.The most important recommendations: Emphasizing the dissemination of cultural awareness of the process of revival and the preservation of the identity and heritage specificity of costume design in light of the attempts of globalization dominance.Keywords: integration, privacy, heritage, trends, contemporary, fashion design.